Anxiety Score in Anxiety Patients Using Slow Deep Breathing Relaxation Therapy - Firmawati, Firmawati; Uyuun, Nur; Rahayu, Sri (Newinera Publisher, 2024)
Anxiety problems experienced can be caused by situations or conditions that a person will face that are considered threatening and endangering themselves so that pharmacological treatment is needed, namely in the form of antianxiety and non-pharmacological. Nonpharmacological therapy in generalist nurses that can be given to anxiety patients includes slow deep breathing. The purpose of this study was to determine the effect of slow deep breathing relaxation therapy on anxiety scores in anxiety patients in the Limboto Health Center working area. The research method used pre-experimental with one group pre-post test design. The study population was patients with anxiety who were in the Limboto Puskesmas working area. The sample in this study was the total population of 15 people. Based on the results showed that the average score of symptoms before slow deep breathing relaxation was 25.73 with a standard deviation of 1.668 and the average score after slow deep breathing relaxation was 15.33 with a standard deviation of 3.222, and the p-value obtained was 0.001 (<α 0.05), meaning that there was an effect of slow deep breathing relaxation therapy on anxiety scores in anxiety patients in the Limboto Puskesmas Working Area.